Mathematics Basic Competency Test in The 3rd Graders of Elementary School - Wahyudi Wahyudi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aimed to describe: (1) the type of errors made by the 3rd graders of Elementary School in Mathematics Basic Competency Test, (2) the cause of error made by the 3rd graders of Elementary School in Mathematics Basic Competency Test. This study was qualitative research. The subject of research was consisted of 3rd graders and teachers of Banyumudal cluster Elementary School, Kebumen Sub District in school year of 2018/2019. Techniques of collecting data used were test, interview, observation, and document. Data analysis was conducted using qualitative analysis involving data reduction, data display, and conclusion drawing or verification. The results of research were as follows (1) Type of errors made the 3rd graders of elementary school in Mathematics Basic Competency Test were: (a) numbers, (b) money, (c) geometry, (d) measurement;  (2) The causes of error made by the 3rd graders of elementary school  are understanding poorly: (a) the name and the symbol of numbers, (b) the order of numbers pattern, (c) place value, (d) the subtraction, multiplication, and division of numbers, (e) mixed count algorithm, (f) the concept of fraction, (g) the conversion of currency, (h) the concept of area, (i) the measurement of length, width, and time.